PENGARUH BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN HOTEL PLAZA SEMARANG - Saputra, Dhany Bagus; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2015)
The service industry is a rapidly growing industry in Semarang. One of which is hospitality services, hospitality businesses spur competition in every party of hotel management to always try to find a breakthrough solution so that the business continues to grow and manage human resources appropriately. This study aims to describe how the variables influence the organizational culture and motivation on employee performance in Hotel Plaza Semarang as well as to determine which variables are the dominant influence of the two variables of organizational culture and motivation on employee performance in Hotel Plaza Semarang. The data in this study were collected through a questionnaire distributed to 50 employees at the Hotel Plaza Semarang. The data collected by using questionnaires which the sampling technique issimple random sampling. Analytical method used in this research is multiple linear regression analysis, using SPSS program.Â These results indicate that the organizational culture in a positive and significant effect on employee performance and motivation in a positive and significant effect on employee performance. Organizational culture and the motivation variable regression coefficient is positive (+) indicates a unidirectional relationship. Empirical finding indicated that to increase employee performance in Hotel Plaza Semarang, the management should pay more attention to organizational culture factors and motivation factors, because those factors proved influence on employee performance.